(untitled) (World Science, 2020)
The results of examination and surgical treatment of 36 patients with cholelithiasis in combination with a hiatal hernia according to the developed algorithm, who were hospitalized and operated on in the clinic from 2014 to 2019, are presented. analysis of the early and long-term results of surgical treatment, it is proved that the surgical treatment of patients with cholelithiasis combined with gastroesophageal reflux disease and hiatal hernia is improved. In practice, the choice of tactics is carried out by the calculation method using the original formula. Thanks to the studies, it was possible to optimize the tactics of surgical treatment of patients with combined pathology.